PEMBELAJARAN TEMATIK INTEGRATIF BERBASIS SOSIOKULTURAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 1 SD N 4 BARENGLOR KLATEN - Ferryka, Putri Zudhah (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2018)
This research for increasing the result through thematic integrative based on sociocultural in theme healthy environment, and sub tema 1. The subject consist of 24 students first class of SD N 4 Barenglor. This research using class action research in two sicluss. The data taken by observation, documentation and the test. The analyse through 3 step reduction data, data, and the result. The result show that the study using tematic integrative based on sociocultural from 6 students has getting KKM (25%) in first cycle increase 15 students (62,5%), and in the second cycle increase 20 students (83,3%). The tematic integratif based on sociocultural in theme 6 healthy environment, and sub tema 1 increasing the students ability in SD N 4 Barenglor